2014
DOI: 10.5539/enrr.v4n4p223
|View full text |Cite
|
Sign up to set email alerts
|

Landscape Mapping to Quantify Degree-of-Freedom, Degree-of-Sprawl, and Degree-of-Goodness of Urban Growth in Hawassa, Ethiopia

Abstract: In the rapidly urbanizing African continent, monitoring, mapping and modeling of urban growth is an indispensable task to understand the magnitude and rate of the ongoing changes. Remote sensing data have been found useful in mapping urban areas and as a source of data for modeling and analysis of spatio-temporal trajectories of cities. In this study, remote sensing data from different sensors extending over a period of 24 years (1987-2011) were used to classify and extract areas of the established land use la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…Other towns have shared a common boundary with a capital city, and they showed a tendency to expand towards Addis Ababa, following the main road, suggesting a lack of rigorous implementation of the master plan. The outcome from prior studies [10,18,37,38,46] indicated that rapid urbanization and lack of good monitoring and managing urban development, lead to a shift in the natural ecosystem of the area and the formation of a more fragmented landscape pattern. In this study, ecological service can be deteriorated due to the considerable decrease in the grassland, agriculture, and vegetation ecosystem (Table 8).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Other towns have shared a common boundary with a capital city, and they showed a tendency to expand towards Addis Ababa, following the main road, suggesting a lack of rigorous implementation of the master plan. The outcome from prior studies [10,18,37,38,46] indicated that rapid urbanization and lack of good monitoring and managing urban development, lead to a shift in the natural ecosystem of the area and the formation of a more fragmented landscape pattern. In this study, ecological service can be deteriorated due to the considerable decrease in the grassland, agriculture, and vegetation ecosystem (Table 8).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Mekelle and Hawassa, are the third and fourth-largest cities, respectively, of the country. These cites lost 20.8% [19] and 48.5% [46] of vegetation cover between the years 1984 to 2014. However, this value was higher in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have identified four areas where we believe additional research is required: (1) understanding the extent and barriers of non-functional systems in all regional states using the land certification system, (2) assessing the causes of non-functionality and feasible options for improvement, (3) how to handle the rise of land that is uninheritable due to its small size, and (4) assessing rural livelihoods in the context of limited land and a growing population. The challenges of peri-urban areas are also of significant importance; however, there is relatively more evidence and on-going research on issues related to this [27][28][29][30][31]. We discuss the four potential research directions in more detail in the following.…”
Section: Implications For Further Researchmentioning
confidence: 99%